Comparison of Students' Mathematical Communication Ability Between Think Pair Share and Numbered Head Together Cooperative Learning Model - Sayekti, Febriyanti; Siagian, Pargaulan (INTEGRASI : Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This study aimed to find out the comparison between students' mathematical communication ability taught by Think Pair Share and Numbered Head Together cooperative learning model. The population in the study were all students in grade X MAN 2 Model Medan. The sample were all students of class X-C with 37 students as experimental class I and class X-H with 36 students as experimental class II, which were selected through random sampling technique. The experimental class I was taught by Think Pair Share cooperative learning model while the experimental class II with Numbered Head Together cooperative learning model. This research was quasi experimental with posttest only control group design. Data collection instrument used was mathematics communication ability test that have been tested for validity and reliability. Before testing the hypothesis, normality test was carried out using Shapiro-Wilk test and homogeinity test using Levene test on the research data. The results showed that the samples came from normal and homogeneous distributed population. Hypothesis testing with t-test show that t_count>t_table(2,4 > 1,666). Thus H_0 is rejected and H_1 is accepted, so students’ mathematical communication ability taught by Think Pair Share cooperative learning model is better than the students’ mathematical communication ability taught by Numbered Head Together cooperative learning model.